Krüppel-like factors compete for promoters and enhancers to fine-tune transcription. Issue 11 (24th May 2017) - Ilsley, Melissa D.; Gillinder, Kevin R.; Magor, Graham W.; Huang, Stephen; Bailey, Timothy L.; Crossley, Merlin; Perkins, Andrew C.
Abstract: Krüppel-like factors (KLFs) are a family of 17 transcription factors characterized by a conserved DNA-binding domain of three zinc fingers and a variable N-terminal domain responsible for recruiting cofactors. KLFs have diverse functions in stem cell biology, embryo patterning, and tissue homoeostasis. KLF1 and related family members function as transcriptional activators via recruitment of co-activators such as EP300, whereas KLF3 and related members act as transcriptional repressors via recruitment of C-terminal Binding Proteins. KLF1 directly activates the Klf3 gene via an erythroid-specific promoter. Herein, we show KLF1 and KLF3 bind common as well as unique sites within the erythroid cell genome by ChIP-seq. We show KLF3 can displace KLF1 from key erythroid gene promoters and enhancers in vivo . Using 4sU RNA labelling and RNA-seq, we show this competition results in reciprocal transcriptional outputs for >50 important genes. Furthermore, Klf3 −/− mice displayed exaggerated recovery from anemic stress and persistent cell cycling consistent with a role for KLF3 in dampening KLF1-driven proliferation. We suggest this study provides a paradigm for how KLFs work in incoherent feed-forward loops or networks to fine-tune transcription and thereby control diverse biological processes such as cell proliferation.